Model‐Based Drug Development: A Rational Approach to Efficiently Accelerate Drug Development. Issue 6 (14th March 2013) - Milligan, P A; Brown, M J; Marchant, B; Martin, S W; van der Graaf, P H; Benson, N; Nucci, G; Nichols, D J; Boyd, R A; Mandema, J W; Krishnaswami, S; Zwillich, S; et al.
<x xml:space="preserve">Abstract</x> The pharmaceutical industry continues to face significant challenges. Very few compounds that enter development reach the marketplace, and the investment required for each success can surpass 1.8 billion. Despite attempts to improve efficiency and increase productivity, total investment continues to rise whereas the output of new medicines declines. With costs increasing exponentially through each development phase, it is failure in phase II and phase III that is most wasteful. In today's development paradigm, late‐stage failure is principally a result of insufficient efficacy. This is manifested as either a failure to differentiate sufficiently from placebo (shown for both novel and precedented mechanisms) or a failure to demonstrate sufficient differentiation from existing compounds. Set in this context, this article will discuss the role model‐based drug development (MBDD) approaches can and do play in accelerating and optimizing compound development strategies through a series of illustrative examples. Clinical Pharmacology & Therapeutics (2013); 93 6, 502–514. doi:10.1038/clpt.2013.54